TSA Printing Worldwide / Nur Emylia Mohd Azzarudin ... [et al.] - Mohd Azzarudin, Nur Emylia; Mustapah Kamal, Nur Athierah; Ismail, Nabilah; Tarmizi, Fatin Nurhayati Ezzati; Hamzi, Hani Nur Yasmin (2022)
TSA Printing Worldwide is a partnership formed by five (5) individuals who hold key positions such as General Manager, Administration Manager, Operational Manager, Marketing Manager, and Financial Manager. The total business capital is RM100,000 with each member contributing RM20,000. Our store sells and provides quality printing services to customers. Every age group can use printing services with various uses such as photocopying school forms, print assignments given by the lecturer and all matters related to offices such as important documents. Our business location is at No.7, Jalan 24/7A,Taman Perindustrian Puchong, Puchong, Selangor. Our vision is to become Malaysia’s most recognized and trusted TSA Printing Worldwide provider. We will use our talents to become widely recognized for our innovation, client loyalty and unwavering integrity. We build our business by challenging the traditional norms of print and marketing media. We will provide fresh ideas and creative solutions for our clients, earning the privilege to be their trusted advisor. Next, our mission is to deliver creative TSA Printing Worldwide provider that make our clients successful. We keep our promises, provide creative solutions, and achieve our client’s goals. We are confident of providing good and quality services in order to maintain the good name of our company. We will also ensure customer loyalty to our store in order to achieve the desired profits. Did you know that the printing industry in the United States is worth about a trillion dollars? This is particularly significant for an industry whose growth is predominantly fueled by the printing of packaging and labels. What's more, do you know what's even more impressive? It's the fact that the worldwide printing market is predicted to be eight times the size of the video game business, and it competes with the gigantic automobile sector. The global printing industry's continued expansion can be due to a number of factors, one of which is how important the services and knowledge they provide are to the success of enterprises. We chose the printing service business because in addition to making a profit, we can also gain new knowledge and new experience. Posters, brochures, flyers, business cards, billboard advertisements, and more are just a few of the several sorts of print that businesses use, and they are all powerful tools for impressing and attracting clients and customers